Children's and adults' perceptions of child necessities in Hong Kong. (20th August 2019) - Lau, Maggie K.W.; Gordon, David; Zhang, Mary F.; Bradshaw, Jonathan
Abstract: There is growing interest in child poverty and well‐being in East Asia. However, empirical studies predominantly adopt "expert‐led" measures (such as adult‐derived child deprivation measures), which usually assume that parents or guardians provide reliable reports about all their children's needs and that the allocation of household resources is effectively equal across all members. Studies of child poverty from a child‐rights or child‐agency perspective are rare in East Asia. Using a consensual deprivation approach, this article examines the extent of agreement between children and adults about which child possessions and activities constitute necessities of life in Hong Kong. The data are drawn from the second wave of the Strategic Public Policy Research project— Trends and Implications of Poverty and Social Disadvantages in Hong Kong: A Multi‐disciplinary and Longitudinal Study. A total of 595 adults and 636 school‐aged children from the first wave of the study were reinterviewed and asked if they considered 16 possessions and activities as essential for children in contemporary Hong Kong. The results showed that adults were significantly more likely to believe that almost all material and social deprivation items were necessities compared with their children, even after controlling for individual‐level factors (i.e., gender and birthplace) and household‐level factors (i.e., number of children in the household, number of working adults, and household income). The findings highlight the importance of incorporating children's views into our understanding of child poverty.